ANIMATION INSTALLATION - Auzani Zeda, Mohamed Kassim (2023)
This project is a joint effort among students enrolled in the GKC2193 Motion Design course. Its objective is to develop an animation display for the FACA Open Day Exhibition, specifically under the Animation Programme. This is an exhibition that displays the Motion design projects created by students. The projects utilise projection mapping to explore various forms of animation canvas.